Scalds and the hazards of hair braiding - The first UK series from a paediatric tertiary burns centre - Ishan Radotra; Nader Henry; Ralph Murphy; Mamta Shah (Elsevier, 2022)
Introduction: Hair braiding is a popular method of hair styling thought to date as far back as 500BC. One of the techniques involves the use of hot water to 'set the braids' which carries the risk of significant scald injury. This study presents the first UK based case series of hair braiding associated scald burns referred to a paediatric tertiary burns centre. Our aim is to increase awareness of this novel mechanism of injury, highlight trends and develop targeted prevention strategies. Methods: Retrospective data collection of patients presenting to a regional paediatric burn centre with hair-braiding associated scald burns was collected over a 13 year period (2007-2020). Patient demographics, mechanism of injury, total body surface area (TBSA), location, depth and distribution were evaluated. The presence of additional family, quality, duration and delay of first aid were also collected. The need for admission and length of hospital stay and long-term outcomes were also appraised. Results: Fourteen patients with scald injuries secondary to hair braiding were identified. The mean age was 6.5 years (5-9) and all patients were female. The most prevalent ethnicity affected were patients with African heritage. The mean TBSA was 3% (1-7 %). First aid was performed in only 50% of cases, of which none was adequate. The distribution of burns was as follows: the back (43%), posterior nape of the neck (36%), posterior shoulder (14%), scalp and face (21.5%) chest (7%) and legs (7%).Nine patients required admission to hospital with the mean length of stay of 2.85 days (range 1-12). No patients required surgery. The mean time to healing was 14 days (range 9-26). Longterm complications included hypopigmentation and hypertrophic scarring requiring scar management strategies. Discussion: This well recognized technique of hair styling carries significant risks of scald injury. Patients often require hospital admission, endure emotional distress and require time off school. Patients can develop significant hypopigmented and hypertrophic scarring at a young age leading to considerable psychosocial morbidity. We recommend spreading awareness of the dangers of hair braiding through education, safety device development, prevention campaigns and targeted outreach work to minimise the hazards of this hair styling technique.